Attitudes and Perceptions of University Students Towards Teachers' Strategies for Managing Large EFL Classrooms - Huseinjon Salimov; Margana; Gultom, Aryadi Manuel (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores students' perceptions and attitudes towards managing large classes in English as a Foreign Language (EFL) at Yogyakarta State University. Using a quantitative survey approach, the research involved 45 master's students from the English Education Department. It examined aspects of classroom management such as physical environment, teacher communication, and instructional strategies. Results show overall positive views on the learning environment and teacher effectiveness but reveal challenges in experiential learning and student-teacher interaction within large classes. The findings emphasize the need for innovative teaching methods, thorough preparation, and tailored lesson plans to address the specific needs of large EFL classrooms. This research offers insights for educators and policymakers to enhance teaching and learning in similar settings